Analisis Determinan Ekspor Minyak Kelapa Sawit Indonesia Pada Negara Asia-6 Tahun 2011-2020 - Gigih Pratomo; Olivia Clara Cantika Saputra (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2022)
Palm oil provides various benefits for the Indonesian economy. Palm oil is an agricultural commodity that is able to absorb labor and generate large foreign exchange from the non-oil and gas sector for Indonesia. Indonesia is the largest palm oil exporter country which is overshadowed by the existence of a pandora box for the welfare of its people (Trade Map, 2022; Pratomo and Rosdiana, 2018). This study aims to determine the determinants of Indonesian palm oil exports to the Philippines, Malaysia, Singapore, Japan, India, and China (Asia-6). This research uses multiple linear regression model with Fixed Effect Model panel data with Indonesian Crude Palm Oil (CPO) export variables, Gross Domestic Product (GDP), exchange rate, and inflation rate. The results showed that the Gross Domestic Product (GDP) had no effect on Indonesia's Crude Palm Oil (CPO) exports to Asia-6 countries. The exchange rate in destination countries has a negative effect on Indonesia's Crude Palm Oil (CPO) exports to Asia-6 countries. Inflation in destination countries has a positive effect on Indonesia's Crude Palm Oil (CPO) exports to Asia-6 countries. High inflation in Asia-6 countries as destination countries is an attraction for Indonesian Crude Palm Oil (CPO) exports which provide high potential profits for the palm oil industry.